Genetic Deletion of Galectin-3 Exacerbates Age-Related Myocardial Hypertrophy and Fibrosis in Mice - Fontana Estevez, Florencia Sofía (2022)
Background/Aims: Aging is accompanied by progressive and adverse cardiac remodeling characterized by myocardial hypertrophy, fibrosis, and dysfunction. We previously reported that galectin-3 (Gal-3) is a critical regulator of inflammation and fibrosis associated with hypertensive heart disease and myocardial infarction. Nevertheless, the role and mechanism of Gal-3 in age-related cardiac remodeling have not been previously investigated. We hypothesized that Gal-3 plays a critical role in cardiac aging and that its deficiency exacerbates the underlying mechanisms of myocardial hypertrophy and fibrosis. Methods: Male C57BL/6 (control) (n=24) and Gal-3 knockout (KO) (n=29) mice were studied at 24 months of age to evaluate the role of Gal-3 in cardiac aging. We assessed 1) survival rate; 2) systolic blood pressure (SBP) by plethysmography; 3) myocardial hypertrophy, apoptosis, and fibrosis by quantification of histological and immunohistochemical analysis; 4) cardiac expression of angiotensin (Ang) II, Ang (1–7) by Radioimmunoassay; 5) transforming growth factor-β (TGF-β), sirtuin (SIRT) 1, SIRT 7 and metalloproteinase 9 (MMP-9) by RT-qPCR and 6) ventricular remodeling and function by echocardiography. Results: We found that aged Gal-3 KO mice had a lower survival rate and exhibited exacerbated myocardial hypertrophy and fibrosis without changes in SBP. Similarly, myocardial apoptosis and MMP-9 mRNA expression was significantly increased in the hearts of Gal-3 KO mice compared to controls. Additionally, cardiac Ang II and TGF-β expression were higher in aged Gal-3 KO mice while SIRT1 and SIRT7 expression were reduced. Conclusion: Our findings strongly suggest that Gal-3 is involved in age-related cardiac remodeling by regulating critical mechanisms associated with the development of pathological hypertrophy. The gene deletion of Gal-3 reduced the lifespan and markedly increased age-dependent mechanisms of myocardial hypertrophy, apoptosis, and fibrosis, including Ang-II, TGF-β, and MMP-9. At the same time, there was diminished cardiac-specific expression of SIRT1 and SIRT7, which are extensively implicated in delaying age-dependent cardiomyopathies.